Development of a Quadrotor Test Bed — Modelling, Parameter Identification, Controller Design and Trajectory Generation. (6th February 2015) - Dong, Wei; Gu, Guo-Ying; Zhu, Xiangyang; Ding, Han
In this paper, a quadrotor test bed is developed. The technical approach for this test bed is firstly proposed by utilizing a commercial quadrotor, a Vicon motion capture system and a ground station. Then, the mathematical model of the quadrotor is formulated considering aerodynamic effects, and the parameter identification approaches for this model are provided accordingly. Based on the developed model and identified parameters, a simulation environment that is consistent with the real system is developed. Subsequently, a flight control strategy and a trajectory generation method, both of which are conceptually and computationally lightweight, are developed and tested in the simulation environment. The developed algorithms are then directly transplanted to the real system, and the experimental results show that their responses in the real-time flights match well with those from the simulations. This indicates that the control algorithms developed for the quadrotor can be preliminarily verified and refined though simulations, and then directly implemented to the real system, which could significantly reduce the experimental risks and costs. Meanwhile, real-time experiments show that the developed flight controller can efficiently stabilize the quadrotor when external disturbances exist, and the trajectory generation approach can provide safe guidance for the quadrotor to fly smoothly through cluttered environments with obstacle rings. All of these features are valuable for real applications, thus demonstrating the feasibility of further development.